Training On the Use of Technology and Communication to Improve the Quality of School Administration Management - Idrus, Ali; Lestari, Agus; Pratama, Robin; Handoko, Yudo; Pratama, Linardo (Proceedings Academic Universitas Jambi, 2026)
Information technology plays a vital role in various public policies, particularly in education, as it enhances the quality of learning and the efficiency of school administration. In Indonesia, the implementation of the Independent Curriculum (Curriculum Merdeka) has led to a shift toward digital learning, requiring collaboration across educational units through platforms provided by the Ministry of Education, Culture, Research, and Technology. SMKN 9 Muaro Jambi, despite having sufficient facilities, still faces challenges in adopting a digital system for school administration. Thus, training in the use of information technology at SMKN 9 Muaro Jambi is essential for improving the efficiency, accuracy, and accessibility of information in administrative tasks. This training aligns with the concept of Independent Learning and Independent Campus (MBKM) and the Key Performance Indicators (IKU) of the University of Jambi, emphasising community service to enhance the quality of education. The primary objective of this community service program (PPM) is to enhance the skills of administrative staff and teachers in utilising school information technology, ensuring its efficient implementation in daily administrative activities, increasing awareness of its benefits, and optimising its use for administrative purposes. By achieving these goals, the PPM program aims to significantly contribute to enhancing the efficiency and effectiveness of administrative management at SMKN 9 Muaro Jambi.